Impacts of Intensified Cropping Systems on Soil Water Use by Spring Wheat. Issue 4 (5th September 2019) - Halvorson, Jonathan J.; Archer, David W.; Liebig, Mark A.; Yeater, Kathleen M.; Tanaka, Donald L.
Abstract : In semiarid dryland farming regions, No‐till and intensified crop rotations may improve water use. Our objective was to determine water use efficiency (WUE) and precipitation use efficiency (PUE) for spring wheat ( Triticum aestivum L.; SW) grown in crop sequences representing different levels of intensification, under minimum (Min‐till) or No‐till. Root zone (0–122 cm) water at planting (SWP) was 2.76 cm higher for two‐ and three‐phase sequences under Min‐till than continuous spring wheat (CSW), and sequences with fallow averaged 2.65 cm higher than those without. Conversely, SWP was unaffected by sequence under No‐till, with less effect of fallow. Root zone water at harvest was unaffected by the number of crop phases or fallow under Min‐till. However, values for CSW exceeded the two‐ or three‐phase sequences by 1.57 and 2.53 cm under No‐till, and sequences without fallow averaged 1.52 cm more than those with fallow. The highest WUE (8.4 kg grain ha −1 mm −1 water) was observed when SW was grown in three‐phase sequences compared with 7.7 kg grain ha −1 mm −1 water, for CSW and SW‐fallow. Spring wheat under Min‐till had higher WUE in sequences with fallow, but no effects of fallow occurred with No‐till. The lowest PUE (near 3 kg grain ha −1 mm −1 precipitation) and no effects of tillage were found in sequences with fallow. However, SW in continuously cropped sequences had PUE between 5.5 and 6.4 kg grain ha −1 mm −1 precipitation and was higher under No‐till. Both WUE and PUE are affected by intensification but may also be influenced by patterns of weather. Core Ideas: Profile water varied as an interaction between crop sequence and tillage. With fallow, soil water changed little the winter prior to planting. Crop water use and yields were lower under continuous cropping than with fallow. Water use efficiency was highest for three‐phase sequences but varied with yield. Continuous cropping resulted in more efficient use of precipitation over the study.